1984
DOI: 10.1258/002367784780891406
|View full text |Cite
|
Sign up to set email alerts
|

Midazolam and fentanyl-fluanisone: assessment of anaesthetic effects in laboratory rodents and rabbits

Abstract: The anaesthetic effects of a combination of midazolam, a water-soluble benzodiazepine, and fentanyl-fluanisone were assessed in laboratory rodents and rabbits. This combination of drugs produced good surgical anaesthesia in all of the species investigated. An important advantage of the combination was that it could be administered as a single intraperitoneal injection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
40
1

Year Published

1987
1987
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(42 citation statements)
references
References 0 publications
1
40
1
Order By: Relevance
“…Eight Wistar rats (70 -80 g; Harlan, Bicester, UK) and ϳ100 female mice aged 6 -12 weeks [BK1 TO strain; Tuck and Son (London, UK) or bred at King's College (London, UK)] were anesthetized as described previously (Flecknell and Mitchell, 1984). The sciatic nerve was exposed and cut in one limb, followed by closure of the skin incision by wound clips.…”
Section: Methodsmentioning
confidence: 99%
“…Eight Wistar rats (70 -80 g; Harlan, Bicester, UK) and ϳ100 female mice aged 6 -12 weeks [BK1 TO strain; Tuck and Son (London, UK) or bred at King's College (London, UK)] were anesthetized as described previously (Flecknell and Mitchell, 1984). The sciatic nerve was exposed and cut in one limb, followed by closure of the skin incision by wound clips.…”
Section: Methodsmentioning
confidence: 99%
“…Fentanyl, in combination with tranquillizers (droperidol or fluanisone) or sedative/hypnotics (etomidate), produces balanced anaesthesia in mice; combinations of low doses of each component can provide analgesia, unconsciousness and muscle relaxation. The advantages of such an approach is that the undesirable side-effects of some agents can be minimized and often results in more effective anaesthesia with fewer secondary effects on major body systems than when using a single agent (Flecknell & Mitchell 1984, Flecknell 1996, Arras et al 2001.…”
mentioning
confidence: 99%
“…We then decided to use fentanyllfluanisone combined with midazolam. This combination has been shown to produce surgical anaesthesia with good muscle relaxation (Flecknell & Mitchell 1984). Previous experience at our laboratory with this combination in rats indicated that it was a stable manageable regimen with a large therapeutic tolerance ISkolleborg et al 1990).…”
mentioning
confidence: 89%